Clinical Case of a Patient with Extranodal Diffuse Large B-Cell Lymphoma and Surgical Complications - Ralitsa Ilieva; Doroteya Todorieva-Todorova; Ivaylo Hristov; Vasilena Tsintsarska (Journal of Biomedical & Clinical Research)
Diffuse large B-cell lymphoma (DLBCL) is one of the most common types of non-Hodgkin lymphoma in adults. In most of the cases a complete remission is possible to obtain by applying conventional immunochemotherapy (rituximab in combination with cyclophosphamide, doxorubicin, vincristine, methylprednisolone or R-CHOP). Its effect depends on some risk factors, cellular origin of the lymphoma and to some extend – the localization when extranodal involvement is confirmed. We present the case of a patient with DLBCL of small intestine and non-specific clinical manifestation. Following treatment with standard therapy R-CHOP patient fail to achieve disease response and gastrointestinal track (GIT) complications were registered.